2021
DOI: 10.1038/s41392-021-00558-8
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L plays a key role in SARS-CoV-2 infection in humans and humanized mice and is a promising target for new drug development

Abstract: To discover new drugs to combat COVID-19, an understanding of the molecular basis of SARS-CoV-2 infection is urgently needed. Here, for the first time, we report the crucial role of cathepsin L (CTSL) in patients with COVID-19. The circulating level of CTSL was elevated after SARS-CoV-2 infection and was positively correlated with disease course and severity. Correspondingly, SARS-CoV-2 pseudovirus infection increased CTSL expression in human cells in vitro and human ACE2 transgenic mice in vivo, while CTSL ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
416
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(436 citation statements)
references
References 57 publications
16
416
0
4
Order By: Relevance
“…The development of small molecule entry inhibitors of SARS-CoV-2 fall behind. Besides the aforementioned chloroquine and arbidol, several small molecule inhibitors targeting host proteases have been explored to inhibit SARS-CoV-2 entry, including TMPRSS2 inhibitors camostat mesylate 16 , nafamostat mesylate 106 , and bromhexine hydrochloride 107 , cathepsin L inhibitors E-64d 16 , 108 , K11777 109 , and SID26681509 110 , and furin inhibitor naphthofluorescein 111 . In general, targeting cellular factors may result in substantial advantages such as a broader range of therapies and reduced chances of developing drug resistance, however, the translational potential of these host protease inhibitors might be limited.…”
Section: Antiviral Therapies Against Sars-cov-2 Cell Entrymentioning
confidence: 99%
“…The development of small molecule entry inhibitors of SARS-CoV-2 fall behind. Besides the aforementioned chloroquine and arbidol, several small molecule inhibitors targeting host proteases have been explored to inhibit SARS-CoV-2 entry, including TMPRSS2 inhibitors camostat mesylate 16 , nafamostat mesylate 106 , and bromhexine hydrochloride 107 , cathepsin L inhibitors E-64d 16 , 108 , K11777 109 , and SID26681509 110 , and furin inhibitor naphthofluorescein 111 . In general, targeting cellular factors may result in substantial advantages such as a broader range of therapies and reduced chances of developing drug resistance, however, the translational potential of these host protease inhibitors might be limited.…”
Section: Antiviral Therapies Against Sars-cov-2 Cell Entrymentioning
confidence: 99%
“…Furin, TMPRSS2 and Cathepsin L are important proteolytic enzyme, which are key regulators of SARS-CoV-2 infection 22,23 . Overexpression of these enzymes facilitates cellular infection.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of Furin/TMPRSS2/Cathepsin L the ten SARS-CoV-2 variants Because Furin, TMPRSS2, and Cathepsin L play important roles in SARS-CoV-2 infection [21][22][23] , mutationrelated structural changes in the virus may in uence the functions of these enzymes. We found that the ability of the D614G reference strain to infect 293T-ACE2 cells was signi cantly increased when Furin, TMPRSS2, or Cathepsin L was overexpressed (Fig 2E).…”
Section: Infectivities Of 10 Sars-cov-2 Variantsmentioning
confidence: 99%
“…Circulating levels of CTSL are increased after SARS-CoV-2 infection where they are positively correlated with disease course and severity [ 18 ] and, importantly, SARS-CoV-2 pseudovirus infection results in increased CTSL expression in human cells in vitro and in human ACE2-transgenic mice in vivo, while CTSL overexpression leads to enhancement of pseudovirus infection in human cells. Moreover, CTSL functionally cleaves the SARS-CoV-2 spike protein leading to enhanced viral entry and amantadine significantly inhibited CTSL activity after SARS-CoV-2 pseudovirus infection both in vitro and in vivo.…”
Section: Adamantanes Against Sars-cov-2: In Vitro and Preclinical Investigationsmentioning
confidence: 99%